2001
DOI: 10.1093/nar/29.24.5169
|View full text |Cite
|
Sign up to set email alerts
|

The genetic organization and evolution of the broad host range mercury resistance plasmid pSB102 isolated from a microbial population residing in the rhizosphere of alfalfa

Abstract: Employing the biparental exogenous plasmid isolation method, conjugative plasmids conferring mercury resistance were isolated from the microbial community of the rhizosphere of field grown alfalfa plants. Five different plasmids were identified, designated pSB101-pSB105. One of the plasmids, pSB102, displayed broad host range (bhr) properties for plasmid replication and transfer unrelated to the known incompatibility (Inc) groups of bhr plasmids IncP-1, IncW, IncN and IncA/C. Nucleotide sequence analysis of pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
125
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(131 citation statements)
references
References 53 publications
3
125
0
3
Order By: Relevance
“…The sequences obtained with the forward primer were identical. The Dyella-like isolates had merA genes that differed somewhat from the closest match, pSB102, a full-sequenced plasmid from Alfalfa rhizosphere (Schneiker et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…The sequences obtained with the forward primer were identical. The Dyella-like isolates had merA genes that differed somewhat from the closest match, pSB102, a full-sequenced plasmid from Alfalfa rhizosphere (Schneiker et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…In mercury contaminated areas, bacteria can exchange plasmids and transposons carrying mercury resistance genes. This event increases the number of resistant bacteria in such environments (28).…”
Section: Discussionmentioning
confidence: 99%
“…Replicon typing and sequencing of the complete plasmid (Tauch et al, 2002) revealed that this cryptic plasmid of a size of approx. 45 kbp was not related to any of the known BHR plasmids except to plasmid pSB102 (Schneiker et al, 2001). Sequencing of plant-associated bacteria revealed that many phytopathogenic and symbiotic bacteria carry plasmids (Vivian et al, 2001;Zhao et al, 2005), pathogenicity islands (Arnold et al, 2003) or integrons (Gillings et al, 2005).…”
Section: Mges In Bacterial Communities Of Agricultural Settings Prevamentioning
confidence: 92%
“…Recipients functioning as a genetic sink, and introduced under laboratory or in situ conditions, have acquired MGEs conferring selectable traits such as mercury or antibiotic resistance from the bacterial fraction of bulk or rhizosphere soil (Drønen et al, 1998;Heuer and Smalla, 2007;Heuer et al, 2002;van Overbeek et al, 2002). Mercury resistance was used as an effective selective marker to exogenously isolate self-transferable plasmids from the phytosphere of different crops in Gram-negative recipients (Lilley and Bailey, 1997;Lilley et al 1994;Schneiker et al, 2001;Smit et al, 1998) or from mercury-polluted soils (Drønen et al, 1998). Capturing degradative genes resident on MGEs has also been successfully demonstrated from soils treated with 2,4-D, but not from untreated controls (Top et al, 1995;.…”
Section: Mges In Bacterial Communities Of Agricultural Settings Prevamentioning
confidence: 99%